The Effect Of Credit To The Inflation Rate Through Gross Domestic Product In Indonesia - Anas Iswanto Anwar; Ali Akbar (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2018)
Credit markets are not always balanced because of unbalanced information and other causes. There are two credit channels that influence the transmission of monetary policy from finance to the real sector, namely bank credit channels that are more concerned with the behavior of banks that are more selective in credit selection because of asymmetric information.This study aims to determine the effect of credit that consists of investment credit, working capital credit and consumption credit to the inflation rate through Gross Domestic Product (GDP) in Indonesia. The overall data used in this study is secondary data from the result of systematic recording in the form of time series from 2007 to 2016 obtained from the Central Bureau of Statistics, Bank Indonesia Report and Indonesian Banking Statistics. Data were analyzed by using multiple regression with Ordinary Least Square (OLS) approach. Based on the results of the research, simultaneous credit has a positive and significant effect on inflation through GDP and partially found that investment credit and working capital credit have positive and significant effect to inflation through GDP, while consumption credit has positive and insignificant effect.